PCR for mecA Gene of Methicillin Resistant Staphylococcus Aureus - Zahan, Nahida Akther; Hossain, MA; Musa, AK; Shamsuzzaman, AK; Mahamud, MC; Mamun, AA; Paul, SK; Ahmed, S; Sumona, AA; Begum, Z; Alam, M; Yusuf, MA; et al. (Mymensingh Medical Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Mymensingh Med J. 2009 Jan;18(1):21-26. The abstract of this article is available on the PubMed website